EDUKASI JADILAH ANAK HEBAT DAN SEHAT DENGAN IMPLEMENTASI 7 KEBIASAAN ANAK INDONESIA HEBAT - Maesaroh, Maesaroh; Prihartini, Ade Rahayu; Khaeriyah, Hana Nurul; Asih, Sari Wulan; Nugraha, Muhammad Fajri Nanda; Rohyati, Rohyati; Al Farizi, Muhammad Imam; Ramadhan, Yahya (Jurnal Pengabdian Mitra Masyarakat, 2025)
The Government of the Republic of Indonesia has a vision to achieve Indonesia Maju Menuju Indonesia Emas 2045 (Indonesia Advancing Towards Golden Indonesia 2045). One of the programs to realize this vision is through the 7 Healthy Habits of Indonesian Children Movement, which is implemented at the primary to secondary education levels. This program is expected to shape the character of the nation's children to be superior and resilient as an effort to prepare superior human resources. This community service activity was conducted in the form of education at SD Negeri Pulopanjang 1 in Serang Regency, Banten, on July 31, 2025, involving 38 students. Pulopanjang is a small island located in Banten Bay. Administratively, the island is part of Serang Regency, Banten, and can be reached by motorboat in approximately 1 hour from Karangantu Port in Serang City or 15–20 minutes from Grenyang Bojonegara Port in Serang Regency. Under the auspices of the Ministry of Basic and Secondary Education, Pulopanjang 1 State Elementary School stands firmly in Kp. Peres, Pulopanjang Village/Subdistrict, Pulo Ampel District, Serang Regency, Banten Province. This state school operates a morning learning system six days a week. This community service initiative is carried out as a form of support for the government's program to promote and implement the “7 Habits of Great Indonesian Children” movement in practice. It also aims to introduce the government's program so that elementary school students can apply these seven good habits. Through the implementation of the 7 Habits of Great Indonesian Children educational program, children gain a clear understanding of how the 7 Habits of Great Indonesian Children program is applied in daily life. It is hoped that with proper understanding, these elementary school students will consistently practice these habits, thereby developing the character of future leaders and becoming outstanding human resources in the future, in line with the government's expectations.